The role of human resource management in improving food security and nutrition toward reducing stunting in Ngada district - Wuli, Rofinus Neto; Rosari, Rosalia Alexandria De (Edelweiss Applied Science and Technology, 2025)
Food security and nutrition are crucial issues that have a direct impact on people’s welfare, especially concerning children’s health, such as stunting. Stunting, which is a condition of growth failure in children due to chronic malnutrition, is one of the main indicators of nutritional problems that need serious attention in Indonesia. This study aims to analyze the role of human resource management in strengthening food security and nutrition to reduce stunting in Ngada Regency. The method used in this research is qualitative, with data collection techniques through literature study, where data is collected by compiling various relevant literature sources into appropriate topics and documents for the purposes of the research proposal. The results show that the role of human resources is crucial in creating a superior agricultural sector to improve food security and nutrition, which in turn reduces the stunting rate in Ngada Regency. Although there is currently a decrease in the stunting rate in Ngada Regency from 2021 to February 2024, this problem still requires serious handling. However, the welfare of farmers in Ngada Regency is still relatively low due to the inadequate quality of farmers’ human resources. Therefore, efforts are needed to improve human resource management, such as through enhancing the quality of education and training in agriculture, increasing farmers’ motivation and welfare, empowering farmer organizations through education and extension, and optimizing cooperation with various parties.